Tribunais paralelos: imprensa e poder judiciário no caso Daniella Perez - Seifert, Priscila Leal (2006)
Much more than a crime of great repercussion, the case Daniella Perez thanks to its long and satiates covering, is the ideal scenery for the study of the complex relationship that settles down between Press and Court. Such relationship can be defined as a competitive symbiosis : at the same time that there are cooperation and complementariety, there is a conflict, related to the way those two instances define their political responsabilities and administer the production of their truths. Face such a noisy crime, the Press accompanied, with attention, the police investigations, the lawsuit and the accused s judgement. Though, its covering didn t privilege the data of the inquiry or of the process. To explain an event that was not explained purely by its facts, the journalists fell back upon a moralizing narrative that emphasized Guilherme s and Paula s monstrous personality. The appeal of the narrative, here, before being considered a method of changing the truth or a form of previus accusation, it is mostly a powerful resource in the construction of the journalists interpretative and descriptive authority about the reality. Under that perspective, information, narrative and moral order are intimately related in the covering of the case Daniella Perez.